2013
DOI: 10.1088/0031-9155/58/18/6317
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of a full-ring multi-lofthole collimator for brain SPECT

Abstract: Currently, clinical brain single photon emission computed tomography (SPECT) is mostly performed using rotating dual-head gamma cameras equipped with low-energy-high-resolution parallel-beam collimators (LEHR PAR). The resolution of these systems is rather poor (8-10 mm) and the rotation of the heavy gamma cameras can introduce misalignment errors. Therefore, we designed a static full-ring multi-lofthole brain SPECT insert for an existing ring of LaBr3 (5% Ce) detectors. The novelty of the design is found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…However, it is possible that one may be able to obtain PET like spatial resolution in brain SPECT and not give up as much in sensitivity. Van Audenhaege et al [14] in simulations determined that by usage of resolution modeling in iterative reconstruction they were able to visualize 4 mm hot-rods when their target resolution was 6 mm at the center of their FOV. Thus it may be that larger apertures than those we determined herein can be employed which would result in improved sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that one may be able to obtain PET like spatial resolution in brain SPECT and not give up as much in sensitivity. Van Audenhaege et al [14] in simulations determined that by usage of resolution modeling in iterative reconstruction they were able to visualize 4 mm hot-rods when their target resolution was 6 mm at the center of their FOV. Thus it may be that larger apertures than those we determined herein can be employed which would result in improved sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the proposal to design and construct such a system dedicated to SPECT brain imaging would be a natural choice [814]. However, the excessive cost of these systems, particularly for imaging procedures utilized less commonly than cardiac perfusion imaging, is likely prohibitive.…”
Section: Introductionmentioning
confidence: 99%
“…56 Multiple-pinhole collimators have also been used for other applications, like cardiac 57-59 and brain SPECT imaging. 20,60 With the arrival of high-resolution detector technologies, different studies have also shown the potential of combining multiple-pinhole collimators and object-minifying pinholedetector geometries. [19][20][21]61,62 Minifying multiple-pinhole collimators allows more projections on the detector, which is beneficial for stationary SPECT systems.…”
Section: A3 (Multiple-)pinhole Collimatorsmentioning
confidence: 99%
“…Noiseless projection data were simulated using an existing GPU-implementation [32] based on a ray-driven forward projector [33], [34] with pinhole subsampling (912 rays in an extended circular area around the pinhole aperture such that photons penetrating the pinhole edge with a probability as low as 0.01 are included [35]). Phantom attenuation and sensitivity are modelled analytically using the Beer-Lambert Law (describing the effect of attenuating tissue on the number of measured counts) and (11) respectively, but without using , as penetration is already modelled.…”
Section: ) Data Generationmentioning
confidence: 99%